Leveraging Wikidata to Build Scholarly Profiles as Service - Lemus-Rojas, Mairelys; Odell, Jere; Brys, Lucille Frances; Ramirez Rojas, Mirian (KULA)

(untitled) (University of Victoria Libraries, 2022)
In this article, the authors share the different methods and tools utilized for supporting the Scholarly Profiles as Service (SPaS) model at Indiana University–Purdue University Indianapolis (IUPUI). Leveraging Wikidata to build a scholarly profile service aligns with interests in supporting open knowledge and provides opportunities to address information inequities. The article accounts for the authors' decision to focus first on profiles for women scholars at the university and provides a detailed case study of how these profiles are created. By describing the processes of delivering the service, the authors hope to inspire other academic libraries to work toward establishing stronger open data connections between academic institutions, their scholars, and their scholars' publications.